2021
DOI: 10.1002/jso.26439
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the prognostic and therapeutic utility of expanded mutation profiling in appendix peritoneal metastasis managed with CRS/HIPEC

Abstract: Introduction: Interrogation of cancers with next-generation sequencing (NGS) mutation panels has become widely utilized, identifying prognostic and actionable mutations. This study explored the value of expanded mutation analysis in appendix peritoneal metastases (APM). Methods: Forty-eight APM patients treated 2013-2018 were retrospectively collected from a registry. Fifty-gene NGS analysis was performed in CLIA approved lab to obtain mutation profiles. All patients underwent cytoreductive surgery (CRS)/hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Finally, pCRC harbored higher rates of VUS in SMAD4 . Davison et al associated SMAD4 protein expression loss with higher tumor grade and worse prognosis in disseminated appendiceal mucinous neoplasms, similar to findings by Zhang et al 35,36 One possible explanation for the increased rates of VUS in pCRC is the higher rates of MSI seen in these samples.…”
Section: Discussionsupporting
confidence: 57%
“…Finally, pCRC harbored higher rates of VUS in SMAD4 . Davison et al associated SMAD4 protein expression loss with higher tumor grade and worse prognosis in disseminated appendiceal mucinous neoplasms, similar to findings by Zhang et al 35,36 One possible explanation for the increased rates of VUS in pCRC is the higher rates of MSI seen in these samples.…”
Section: Discussionsupporting
confidence: 57%
“…Identifying surrogate factors that can be identified before CRS/HIPEC will be important tools in the future. Some potential tools actively being investigated include serologic markers and mutation profiles 2,29,70,71,72 …”
Section: Appendiceal Peritoneal Metastasis Managementmentioning
confidence: 99%
“…These tools currently have a role in colon cancer to identify tumors unresponsive to anti‐EGFR therapy that harbor KRAS and BRAF mutations in metastatic CRC as well as emerging data that, when combined with primary tumor sidedness, may have a predictive role in metastatic CRC outcome 190‐193 . Recent exploratory studies in appendix cancer PM has identified SMAD4 and P53 as surrogates of more aggressive biology 70 …”
Section: The Future Of Peritoneal Metastasis Managementmentioning
confidence: 99%
See 2 more Smart Citations